2021
DOI: 10.1002/jcv2.12022
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral inhibition and dual mechanisms of anxiety risk: Disentangling neural correlates of proactive and reactive control

Abstract: Background Behavioral inhibition (BI) is a temperament style characterized by heightened reactivity and negative affect in response to novel people and situations, and it predicts anxiety problems later in life. However, not all BI children develop anxiety problems, and mounting evidence suggests that how one manages their cognitive resources (cognitive control) influences anxiety risk. The present study tests whether more (proactive control) or less (reactive control) planful cognitive strategies moderate rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 90 publications
2
10
1
Order By: Relevance
“…Finally, although P1 angry and happy biases interacted with linear time to predict anxiety (as discussed above), no direct bivariate correlations between ERP amplitudes and anxiety or BI were found. An effect of emotion was found for P1 amplitude, with amplitude to happy and angry faces higher than amplitude to neutral faces, replicating recent research in young children (e.g ( Valadez et al, 2021 ). No effect of emotion was found for P2 or N2, which again is relatively consistent with previous findings, although research in this area with preschool-aged children is scarce ( Bar-Haim et al, 2005 , Kanske et al, 2011 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, although P1 angry and happy biases interacted with linear time to predict anxiety (as discussed above), no direct bivariate correlations between ERP amplitudes and anxiety or BI were found. An effect of emotion was found for P1 amplitude, with amplitude to happy and angry faces higher than amplitude to neutral faces, replicating recent research in young children (e.g ( Valadez et al, 2021 ). No effect of emotion was found for P2 or N2, which again is relatively consistent with previous findings, although research in this area with preschool-aged children is scarce ( Bar-Haim et al, 2005 , Kanske et al, 2011 ).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, for high BI children, anxiety risk appears to be lowest when children require relatively little effort to implement planful control processes. This interpretation is necessarily speculative, but the results clearly indicate that, even in young children, attentional control processes are important moderators of anxiety risk in the context of high BI, which is nicely consistent with the latest theory and research with older children ( Fox et al, 2021 , Troller-Renfree et al, 2019 , Valadez et al, 2021 , White et al, 2011 ).…”
Section: Discussionsupporting
confidence: 81%
“…Valadez et al. (2021) examined ERPs drawn from EEG data that were simultaneously collected during the 15‐year administration of the AX‐CPT. Using separate cue‐ and probe‐locked ERPs, they found that BI was associated with anxiety only among youth who tended not to differentiate between cues during the earlier cue period (indicating a less proactive strategy) but instead differentiated between them during the later probe period (indicating a more reactive strategy).…”
Section: The Detection and Dual Control Moderators Of Temperament And...mentioning
confidence: 99%
“…Likewise, a recent study identified a subgroup of children for whom enhanced inhibition ability coincided with higher anxiety symptoms after accounting for prefrontal cortex-amygdala connectivity [ 84 ]. Similarly, greater trait and social anxiety corresponded with enhanced cognitive control capacities among youths after adjusting for their electroencephalography (EEG) brainwave patterns and temperament [ 85 ]. Also, the overgeneralized control model hypothesizes that some subgroups of individuals might show negative or non-linear (e.g., inverted U-shaped) connections between EF and anxiety constructs across time [ 27 , 86 ].…”
Section: Overgeneralized Control Model Of Ef- and Anxiety-related Con...mentioning
confidence: 99%